Empirical analysis of the impact of monetary policy through interest rates on economic growth in Indonesia - Hamzah, Muh. Qardawi; Ruslan , Andi; Ashari, Ihsan (Priviet Social Sciences Journal, 2026)
This study investigates how inflation and monetary policy, as reflected in the policy interest rate (BI Rate), affect Indonesia's economic growth, as indicated by the GDP. Multiple linear regression analysis was employed to discover connections between independent and dependent variables in an economic setting. The analysis's findings indicate that neither the BI Rate nor inflation significantly affects GDP growth. Although not sufficiently strong to be regarded as statistically significant, the positive coefficients derived from both variables show a propensity for increases in inflation and policy interest rates to enhance economic growth. The significance of the interaction between the two variables in monetary policy is confirmed by simultaneous analysis, which reveals that both inflation and the BI Rate significantly contribute to GDP variance when examined together. These results suggest that monetary policy must work in tandem with fiscal policy and the real sector, as well as be adaptively managed to respond to changes in the global economy to effectively stimulate economic growth in Indonesia [2]. This study is anticipated to significantly aid policymakers in developing more potent plans to accomplish sustainable growth and national economic stability.